Multiculturalism: Indonesianism Discourse and Interpretation - Mahfudz Junaedi (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2018)
Multiculturalism has been a discourse and debate up until now, and has not been completed, particularly in the context of Indonesian-ness. Muslims see it is not monolithic but diverse, pluralistic Indonesian society split into two groups, those who reject multiculturalism and those who receive it. The group rejected the thought that the discourse and ideology of multiculturalism and its derivative, suchas democracy, human rights is a product of Western secular inconsistent with Islam. While the group received based on the ideas and basic pendangan that diversity asa fact and reality be natural and it is the will of God, even fighting stance within the framework of solidarity and equality in a beautiful building living systems and among fellow creatures of God. Both groups, ' an impressive glimpse the truth ofthe argument respectively. In this condition, the commentators also have diverse views in memahamai multiculturalism. This paper specifically explore multikuturalisme as a concept is still debated and discourse for Muslims; In the Al-Qur’an there are verses that support an impressive glimpse of the concept of multiculturalism and reject impression; The presence of the interpretation of the Al-Qur’an Indonesian context, such as Hamka and Quraish Shihab as an authoritative figure in the field of interpretation Indonesia, deserves to be a reference. Configuring a plural society or compound that has potential in the development of behavioral inclination conflict and disintegration among various groups, interethnic. In addition, there is a tendency of the presence of the integrative power as asource of social change dynamics and plurality of society, because most conflictsand violence in Indonesia 'religion' (interpretation of the sacred text) is consideredto be one of the factors that have contributed to the trigger. Religion and belief systems influence on the behavior and mindset of a person or people adherents, both positive and negative. Some theories, either grand theory, middle theory, and aplicative theory used as a knife analysis, including studies of sociological theory developed by Max Weber, that mindset, behavior, ethics and world view society is influenced by a belief system that believes. Thomas EO dea also argues that religionis not only contributing factor for the integration of society, but he also has thedivisive nature (disintegrative) as an initial cause of tension and conflict. The expected results, that the diversity of human identity, whatever it is, whether cultural, ethnic nationality and gender in view of the Quran is an equivalent, equal.